Integrated Owner Identity And Retail Communication Strategies In Shaping Consumer Purchase Decisions - Nabila Hafizhah; La Mani (Lembaga Bale Literasi, 2026)
Retail environments increasingly function as communicationspaces where identity, symbolism, and experience influence consumer perceptions and behaviour. Despite extensive research on marketing and consumer decision making, limited studies have examined how owner identity, personal branding, store atmosphere, and store location operate as integrated communication elements shaping purchasing decisions. This study aims to analyse how these elements function as strategic communication drivers within a retail context and how they influence consumer purchase behaviour. The research adopts a quantitative approach using survey data collected from consumers who have interacted with a retail fashion environment. Data were analysed using multiple regression to examine both partial and simultaneous effects of communication-related variables on purchase decisions. The analysis focuses on how identity representation, visual branding, spatial design, and experiential cues contribute to consumer evaluation and decision processes. The findings reveal that owner identity, personal branding, store atmosphere, and location significantly influence purchase decisions both individually and collectively. Store location emerges as the most dominant factor, followed by atmosphere and personal branding, indicating the importance of spatial accessibility and experiential communication in shaping consumer responses. Owner identity also contributes by strengthening credibility and emotional connection between consumers and the retail brand. This study demonstrates that retail settings operate not only as commercial spaces but also as communication ecosystems in which symbolic identity, environmental cues, and experiential interaction collectively shape consumer trust and behavioural intention. The findings highlight the importance of integrating identity-based communication, experiential design, and spatial strategy to strengthen retail competitiveness and consumer engagement.